The Relationship of Knowledge and Attitudes of Pregnant Women About Balanced Nutrition to the Fulfillment of Nutrition During Pregnancy - Efi Satriana Silalahi (Pena Cendekia Insani, 2021)
Introduction: In the maintenance and health of the mother, as well as supplies for the lactation period, both for the fetus and the mother (for example, the supply of iron, protein and calcium ). The most important thing for pregnant women is not quantity but food quality. Food should be balanced and contain a sufficient amount of all nutrients. This study aims to analyze the relationship between the knowledge and attitudes of pregnant women about balanced nutrition to the fulfilment of nutrition during pregnancy at the Citra Clinic. Method: This type of research is a survey that is analytical and descriptive with a cross-sectional approach. The population in this study were pregnant women who came to Citra's primary clinic to check on pregnancy. The study sample was 60 people with total sampling techniques and chi-square data analysis. The results showed that the knowledge and attitudes of pregnant women about balanced nutrition are related to the fulfilment of nutrition during pregnancy. Result : From the results of the study, it is known that (0.001 < ? = 0.05 ho, being rejected means that there is a relationship between the knowledge period of pregnancy, the need for nutrients increases to meet the needs of fetal growth and development, and attitudes of pregnant women about balanced nutrition towards the fulfilment of nutrition during pregnancy..